Bangladesh : Enhancing Coastal Resilience in a Changing Climate - Kazi, Swarna; Urrutia, Ignacio; van Ledden, Mathijs; Laboyrie, Jean Henry; Verschuur, Jasper; Haque Khan, Zahir-ul; Jongejan, Ruben; Lendering, Kasper; Mancheño, Alejandra Gijón (World Bank, Washington, DC, 2022)
As the World Bank and government of Bangladesh celebrate 50 years of development cooperation this year, a key highlight is the journey towards addressing climate change and improving the resilience of the coastal zone. From the outset, the World Bank has been a long-standing partner in the government’s efforts to reduce the risks from disasters and enhance coastal resilience, resulting in a number of noteworthy achievements. Bangladesh demonstrated how investments in the entire chain of disaster risk reduction saves lives, reduces economic losses, and protects development gains. Proactive policies and sound investments in strengthening resilience across multiple fronts over the last five decades have resulted in a drastic decline in the number of casualties from cyclones. Bangladesh’s approach has been an integrated one, from grassroots strengthening of community-level adaptation and community-based early warning systems, to investing in key protective infrastructure and promoting innovations, all founded on a strategic policy framework. With the success of these initiatives, Bangladesh has emerged as a global leader in climate resilience. Although there has been significant progress, with the coastal population and economy expected to grow, and the intensity and magnitude of extreme events projected to increase due to climate change, hazard impacts still pose a great threat to the development ambitions of the country. Thus, further actions are needed to improve the resilience of the coastal zone. This report provides new perspectives and insights into how to address the impacts of climate-related hazards in the coastal zone. The report provides evidence of the drivers of risks in Bangladesh’s coastal zone, analyzes what has been achieved so far in reducing these risks, and reviews the lessons learned from these achievements. Supported by in-depth analytical work, the report explores innovative solutions illustrated with artist impressions and puts forward seven key recommendations to enhance coastal resilience in Bangladesh and build shared prosperity for decades to come. What is clear from the report is that investing in coastal resilience will bring multiple benefits, and that the time to act is now.